2000
DOI: 10.1038/sj.onc.1203464
|View full text |Cite
|
Sign up to set email alerts
|

Activity of MDM2, a ubiquitin ligase, toward p53 or itself is dependent on the RING finger domain of the ligase

Abstract: We previously showed that oncoprotein MDM2 has ubiquitin ligase activity toward tumor suppressor p53. In that paper, we showed very weak homology in the carboxyl terminal portion between MDM2 and E6AP (HECT domain). We mutated the cysteine residue (C464) corresponding to the residue essential for the ubiquitin ligase activity of E6AP and this mutation diminished the ligase activity of MDM2. The cysteine residue described above is also one of the cysteine residues that form the RING ®nger domain of MDM2. We tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
266
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 341 publications
(276 citation statements)
references
References 19 publications
8
266
1
1
Order By: Relevance
“…It was indeed shown that, besides the ability of Mdm2 to bind p53 in its transactivation domain and to interfere with p53 transcriptional activity, Mdm2 acts as an E3 ubiquitin ligase responsible for the ubiquitination of p53 and itself. [15][16][17] It was later proposed that Mdm2 mediates monomeric p53 ubiquitination on multiple lysine residues, rather than polyubiquitination, as previously thought. 18 Because chains of multiple ubiquitin molecules are necessary for efficient protein degradation, the data suggested that the enzymatic activity of Mdm2 might not be sufficient for optimal degradation of p53, and that other proteins must aid in polyubiquitination and degradation of p53 in vivo.…”
Section: Introductionmentioning
confidence: 92%
“…It was indeed shown that, besides the ability of Mdm2 to bind p53 in its transactivation domain and to interfere with p53 transcriptional activity, Mdm2 acts as an E3 ubiquitin ligase responsible for the ubiquitination of p53 and itself. [15][16][17] It was later proposed that Mdm2 mediates monomeric p53 ubiquitination on multiple lysine residues, rather than polyubiquitination, as previously thought. 18 Because chains of multiple ubiquitin molecules are necessary for efficient protein degradation, the data suggested that the enzymatic activity of Mdm2 might not be sufficient for optimal degradation of p53, and that other proteins must aid in polyubiquitination and degradation of p53 in vivo.…”
Section: Introductionmentioning
confidence: 92%
“…13 The Mdm2 protein is the first p53 E3-ubiquitin ligase described, and induces p53 polyubiquitination and degradation when overexpressed. [14][15][16][17] More recently, the idea that Mdm2 mediates monomeric p53 ubiquitination on multiple lysine residues rather than poly-ubiquitination has been proposed. 18 As chains of multiple ubiquitin molecules are necessary for efficient protein degradation, the data suggested that Mdm2 might not be sufficient for optimal degradation of p53, and that other proteins must aid in polyubiquitination and degradation of p53 in vivo.…”
Section: Constitutive Degradation Of P53 Is Strictly Dependent On Mdm2mentioning
confidence: 99%
“…Mdm2 can inhibit p53 activity by binding to its transactivation domain, and through promoting the proteasomal degradation of p53 by acting as an E3 ligase (Fang et al, 2000;Honda and Yasuda, 2000;Michael and Oren, 2003). In mice, knockout of Mdm2 increases p53 protein levels and overall transactivation activity in both proliferating and post-mitotic cells.…”
Section: Introductionmentioning
confidence: 99%